The Impact of International Migration on Skills Supply and Demand in South Africa - Derek Yu (African Human Mobility Review, 2022)
This study investigated the demographic, education and labour market characteristics of three groups: (1) immigrants into South Africa; (2) natives who remained in the country; (3) emigrants into the top five destination countries (Australia, Canada, New Zealand, the UK and USA). The empirical findings were used to examine the extent of migration to and from the country, from the perspectives of skills supply and demand. Emigrants were most educated, enjoyed the lowest unemployment probability (about 10%), and were most likely to be involved in high-paying skilled occupations and tertiary sector activities as full-time employees (if employed). The immigrants fared worse than the emigrants but better than natives. These immigrants, mainly originating from the other African countries, were slightly more educated, but enjoyed higher LFPR (75%) and lower unemployment likelihood (20%), compared with the natives (55% and 30% respectively). Furthermore, for both above-mentioned two groups, they were distinguished into long-term, medium-term and short-term migrants, and it was found that long-term migrants fared relatively better in the labour markets of their respective host countries. Overall, the findings strongly indicated brain drain out of South Africa, and exodus of highly educated and skilled people is not complemented by a rapid increase of supply of equally educated and skilled labour force entrants in the country. The study recommended four policy suggestions: ease up regulations to attract skilled immigrants, promote entrepreneurial activities of immigrants, better develop and retain skills of the natives, improve migration and vacancy data capture, availability, usage and analysis.